1998
DOI: 10.2108/zsj.15.263
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical and Ultrastructural Identification of Pituitary Cell Types in the Protogynous Thalassoma duperrey during Adult Sexual Ontogeny

Abstract: Protogynous wrasses (Thalassoma duperrey): females (F), primary males (PM) along with a few terminal-phase males (TM) and sex-changed males (SM), were used to characterize the topographical organization of the pituitary. In general, immunocytochemical and ultrastructural features of the adenohypophyseal cell types of the saddleback wrasse pituitary resemble those of other teleosts. In the rostral pars distalis (RPD), corticotropic cells were found bordering the neurohypophysis (NH) and surrounding the centrove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 59 publications
4
9
0
1
Order By: Relevance
“…GH cells were located mainly in the dorsal central PD and were arranged in thin strands in the ventral part of A. gigas pituitary gland. This distribution is in agreement with other teleosts, as reported previously (see Ball and Baker 1969;Holmes and Ball 1974;Schreibman et al 1973) and in more recent studies (Parhar et al 1998;Rendón et al 1997;Rodríguez-Gómez et al 2001;Sánchez Cala et al 2003;Segura-Noguera et al 2000;Vissio et al 1997), although some variations may occur, depending on the species and developmental stage (García-Hernández et al 1996;Villaplana et al 2000;Sánchez Cala et al 2003).…”
Section: Structure Of the Pituitary Glandsupporting
confidence: 93%
See 1 more Smart Citation
“…GH cells were located mainly in the dorsal central PD and were arranged in thin strands in the ventral part of A. gigas pituitary gland. This distribution is in agreement with other teleosts, as reported previously (see Ball and Baker 1969;Holmes and Ball 1974;Schreibman et al 1973) and in more recent studies (Parhar et al 1998;Rendón et al 1997;Rodríguez-Gómez et al 2001;Sánchez Cala et al 2003;Segura-Noguera et al 2000;Vissio et al 1997), although some variations may occur, depending on the species and developmental stage (García-Hernández et al 1996;Villaplana et al 2000;Sánchez Cala et al 2003).…”
Section: Structure Of the Pituitary Glandsupporting
confidence: 93%
“…These cells have previously been demonstrated in the RDP of many other teleosts (Arana et al 1997;Batten 1986;Parhar et al 1998;Rodríguez-Gómez et al 2001;Sánchez Cala et al 2003;Segura-Noguera et al 2000), where they were arranged as a compact mass, in follicles, in both, or in thick strands (see Agulleiro et al 2006). The follicular arrangement of PRL cells present in salmonids and ancient teleost species such as the eel (Arakawa et al 1992;Grandi et al 2003;Ingleton and Stribley 1977), which is considered a basal feature, was not found in A. gigas pituitary.…”
Section: Structure Of the Pituitary Glandmentioning
confidence: 69%
“…Human β-TSH antisera have been reported to cross-react well with teleost TSH (for a review, see Agulleiro et al 2006); this has also been found here in tilapia. We have not observed cross-reactivity between antisera to β-TSH and GTH II (β-LH) as described in several studies (García-Hernández et al 1996;Parhar et al 1998;Segura-Noguera et al 2000) but between the antisera directed against GTH I and GTH II. A moderate crossreactivity (10% and 12%, respectively) between these antisera has previously been observed (Suzuki et al 1988).…”
Section: Discussionsupporting
confidence: 75%
“…A few more extensive studies have been performed (e.g. García-Hernández et al 1996;Grandi and Chicca 2004;Laiz-Carrión et al 2003;Naito et al 1993;Parhar et al 1998Parhar et al , 2002Sánchez Cala et al 2003;Segura-Noguera et al 2000;Weltzien et al 2003b;Yan and Thomas 1991) but no thorough investigation has localised all pituitary hormones by immunohistochemistry on consecutive sections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation